Constructing fully carbon-based fillers with a hierarchical structure to fabricate highly thermally conductive polyimide nanocomposites. Issue 23 (22nd May 2019) - Guo, Yongqiang; Ruan, Kunpeng; Yang, Xutong; Ma, Tengbo; Kong, Jie; Wu, Nannan; Zhang, Jiaoxia; Gu, Junwei; Guo, Zhanhu
Abstract : Fully carbon-based f-MWCNT- g -rGO with a hierarchical structure was built to fabricate highly thermally conductive polyimide nanocomposites by electrospinning. Abstract : A novel kind of fully carbon-based filler (f-MWCNT- g -rGO) is constructed by a reaction between melted urea functionalized multi-walled carbon nanotubes (f-MWCNTs) and graphene oxide (GO) followed by chemical reduction. The corresponding highly thermally conductive polyimide (f-MWCNT- g -rGO/PI) nanocomposites are then fabricated through the combined method of in situ polymerization, electrospinning and hot pressing. An improved thermal conduction model is also proposed and established considering the filler/matrix interfaces, filler dispersion and alignment, etc. The f-MWCNT- g -rGO fillers have a hierarchical "line-plane" structure. The fabricated f-MWCNT- g -rGO/PI nanocomposites possess an outstanding thermal conductivity coefficient ( λ ), and excellent thermal stabilities and mechanical properties. Specifically, the f-MWCNT- g -rGO/PI nanocomposites reach the maximum λ of 1.60 W m −1 K −1 at a relatively low loading of f-MWCNT- g -rGO fillers (10 wt%, the mass ratio of rGO to f-MWCNT is 2 : 1). In addition, the theoretical λ value calculated by our established thermal conduction model is more in line with the experimental λ values compared with other traditional models. Owing to the high thermal conductivities while preserving good mechanical properties and thermal stabilities at a relatively low loading of f-MWCNT- g -rGO filler, the f-MWCNT- g -rGO/PI nanocomposites are expected to be used as thermal pads in light emitting diode (LED) substrates and liquid crystal displays.